Valorizando a diversidade: desenvolvimento da liderança inclusiva e impacto sobre o engajamento no trabalho - Andretta, Danilo (2024)
Valuing diversity and inclusion has become increasingly present in the speeches of managers in organizations. Faced with a growing interest in the diversity agenda, in this thesis we have shed light on the inclusive leadership style. According to the literature, inclusive leader promotes the uniqueness of followers, strengthens the sense of belonging in a team, shows appreciation for individual contributions, and supports organizational efforts towards inclusion. Thus, a look at diversity management practices represents a central element in understanding inclusive leadership. In this context, I developed this thesis from three studies that explored different aspects of inclusive leadership. In the first study, we carried out an integrative literature review based on leadership development from the perspective of diversity and inclusion. The research revealed four thematic axes that indicate different paths in this literature, but which are intertwined. In addition, we proposed a conceptual model based on the contributions of the literature with two central elements: the leader profile and the objectives of the program, involved by the organization context and culture. In the second study, we examined the impact of inclusive leadership on work engagement through the effect of the leader's ethical behavior, the relationship between which is conditioned by the leader's reputation for results. This study shed light on work engagement as one of the potential outcomes of inclusive leadership, based on signaling theory, and included a sample of 221 followers. We found that inclusive leaders are seen by their followers as more ethical leaders, and that this relationship culminates in a higher level of work engagement. The third study aimed to examine whether the impact of inclusive leadership on work engagement only occurs when the team members recognize the leader as inclusive. Additionally, we assessed whether the level of the leader's commitment to promoting equality represents a strategy that strengthens the relationship between self-assessment and the perceptions of followers about inclusive leadership. The third survey involved 41 leaders and 161 followers, and the theoretical model was discussed in the light of impression management theory. We revealed that the leader's selfidentification with the inclusive leadership style is not enough to arouse work engagement, as this relationship depends on the followers' recognition that this leader is inclusive and values diversity. Taken together, the research carried out in this thesis reflects on the relevance and timeliness of inclusive leadership. This literature can continue to foster significant transformations in the workplace, aiming at the construction of fairer, more egalitarian, and sustainable organizations that value human beings.